Hematopoietic stem cell transplantation in children with acute myeloid leukemia - Z. M. Dyshlevaya; M. M. Shneider; L. N. Shelihova; Y. V. Skvorzova; E. V. Skorobogatova; A. A. Maschan (Онкогематология)
.